2015
DOI: 10.1007/s11418-015-0924-6
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Ophiopogon and Liriope tubers based on DNA sequences

Abstract: Ophiopogon japonicus is a herbaceous perennial plant in Liliaceae, and its tubers are used in traditional Japanese medicine as Bakumondo, prescribed for treating cough, sputum, and thirst. Liriope is a genus of ornamental plants related to Ophiopogon, and its tubers are used in folk medicine as well. Although tubers from both genera are traded in Korean and Chinese markets, only O. japonicus is defined as the plant of origin for Bakumondo in the Japanese Pharmacopoeia [1], and Liriope tubers cannot legally be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…5,8-Dimethoxy-6-methyl-7-hydroxy-3-3(2-hydroxy-4-methoxybenzyl)chroman-4-one (58-F) is a flavanone and a novel compound extracted from the traditional Chinese herb Ophiopogon japonicas, which is widely distributed and used clinically in mainland China1011.…”
mentioning
confidence: 99%
“…5,8-Dimethoxy-6-methyl-7-hydroxy-3-3(2-hydroxy-4-methoxybenzyl)chroman-4-one (58-F) is a flavanone and a novel compound extracted from the traditional Chinese herb Ophiopogon japonicas, which is widely distributed and used clinically in mainland China1011.…”
mentioning
confidence: 99%
“…Oxidative stress sensitizes hepatocytes to either calcium overload 29 or HMGB1 release. 30 Although HMGB1 and calcium have been separately reported to be important mediators of oxidative stress-induced injury, the potential relationship between them remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings support this hypothesis, demonstrating that SOCE activation leads to a cytosolic calcium increase and HMGB1 release from cells after H 2 O 2 treatment. In addition, the compound 5,8-dimethoxy-6-methyl-7-hydroxy-3-3(2-hydroxy-4-methoxybenzyl) chroman-4-one (58-F) is a flavanone extracted from Ophiopogon japonicas, which has been widely distributed and used clinically in mainland China, 29,31 and we recently reported that 58-F protects against ROS-induced liver injury. 32 In the present study, we explore the protective contribution of 58-F to H 2 O 2 -induced calcium homoeostasis and HMGB1 release.…”
Section: Introductionmentioning
confidence: 99%
“…For ZMD, genomic and transcriptomic studies have not yet been reported; only a study discriminating O . japonicus and Liriope spicata (“shanmaidong”) has been published, which used DNA sequences 23, 24 and EST-SSR markers 25 or SCAR markers 26 to study molecular diversity in the two species. ZMD usually requires three years from planting to harvest; according to the history of planting, ZMD tubers will gradually decay and disappear after three years.…”
Section: Introductionmentioning
confidence: 99%